Indonesia’s 2022 Presidency for the G20 Summit in a Strategic Intelligence Perspective Anticipating Security and Hidden Agenda Issues - Sundawan SALYA; Yassar NANDANA (International Journal of Environmental, Sustainability, and Social Science, 2022)
Indonesia is trusted to host the G20 summit in 2022. This opportunity is the first time since the G20 was established. With the slogan "Recover Together, Recover Stronger", Indonesia hopes that this forum will provide an opportunity for all member countries to engage in dialogue to achieve political stability following the Covid-19 pandemics. Several priority issues will be discussed, which is the global health architecture as a joint effort in responding to Covid-19, which is still spreading in various countries, including the emergence of a new virus variant known as Omicron. In addition to these issues, dialogue forums allow countries to aspire to their national interests, although not all state purposes and interests can be stated explicitly. Strategic intelligence provides remarkable analytical results. Undeniably, the Indonesian Presidency in the G20 has many advantages. However, that does not mean it negates some threats. The holding of the G20 in Indonesia presents a potential threat in increasing clandestine operations in Indonesian territory, obtaining information domestically as a manifestation of foreign efforts to achieve their national interests. In addition, the discussion of sensitive issues such as the issue of Papuan independence, issues of illegal logging and conservation and destruction of forests can irritate Indonesia and interfere with the national interests. Thus, the strategic intelligence approach for maintaining Indonesia's interests in the G20 series should be well-applied.